Basics with Babish : recipes for screwing up, trying again, and hitting it out of the park - Rea, Andrew; Choung, Susan; Beach, Kendall (Simon Element, 2023)
Over 100 easy-to-follow recipes that teach you how to learn from your mistakes and become a better cook, from the culinary genius who created the Babish Culinary Universe YouTube channel in this long-awaited companion. In his wildly popular Basics with Babish series, YouTube star Andrew Rea, who has amassed millions of subscribers, attempts, often fails, but always teaches cooking techniques for all levels of cooks. He's explained everything from how to make challah bread and English muffins to Asian dumplings and homemade bacon. Now those classic, essential recipes (and many more) are compiled into an authoritative cookbook which contains hundreds of step-by-step photographs with tips and tricks to help you troubleshoot anything from broken butter to burnt bread to bony branzino. Basics with Babish isn't just a kitchen Bible for a new generation of home chefs, it's a proud reclamation of mistakes which encourages you to learn from your and Andrew's missteps alike.